P120 Intraoperative frozen section could be misleading in the diagnostic evaluation of ovarian granulosa cell tumors. (1st November 2019) - Di Cello, A; Visconti, F; Bitonti, G; Cefalì, K; Ranieri, K; Zullo, F; Roberta, V; Di Carlo, C
Abstract : Introduction/Background: Intra-operative frozen section (IFS) can provide an instinct guide for treatment of ovarian tumors intra-operatively, though limitations exist. We aimed to determine the value of IFS and US in the diagnosis of ovarian granulosa cell tumors. Methodology: A retrospective review of granulosa cell tumors (GCTs) surgically treated at our Unit, between June 2006 and March 2019, was done. The diagnostic performance of ultrasound (US) and malignant IFS diagnosis was evaluated. Data of 20 patients were reviewed. Intra-operative FS and US results were compared with the definitive surgical diagnosis. Surgical data were reviewed and analyzed. Results: A total of 12 cases were correctly identified at the intraoperative FS as ovarian granulosa tumors. There were 8 (32%) false negative diagnoses. According to well defined parameters, all 20 cases were correctly suspected as ovarian GCTs at US. About surgical treatment, in 12 women with positive FS the appropriate surgical staging was performed. In 8 women with negative FS surgical treatment was variable: 4 women underwent laparoscopic salpingo-oophorectomy and the surgical staging was completed after definitive surgical diagnosis; hysterectomy and bilateral salpingo-oophorectomy was performed in 2 patients; the conservative surgery on the healthy ovary was performed in the remaining 2 patients. Conclusion: This study concluded that FS appears to be an inadequate technique for the histopathological diagnosis of ovarian GCTs, while the US features are really suggestive allowing a right clinical suspicious. Perhaps, when an ovarian GCTs is suspected at the US, intraoperative FS could be misleading and could lead to an inappropriate surgical management. Disclosure: Nothing to disclose.